CARBOHYDRATE AND LIPID METABOLISMS IN PREGNANT WOMEN WITH EXCESSIVE GESTATIONAL WEIGHT GAIN - Ostafiichuk, S.O.; Prudnikov, P.M.; Volosovskiy, P.R.; Henyk, N.I. (World of Medicine and Biology, 2022)
During pregnancy, the changes in carbohydrate and lipid metabolisms are determined by the level of gestational weight gain independent of the prepregnancy weight. In excessive weight gain women’s insulin concentration and insulin resistance index in the third trimester were higher compared to the early terms (p